Social school contacts of multibacillary leprosy cases in children living in the hyperendemic region of the Midwest of Brazil - Camila Massae Sato; Thaisa da Silva Vargas Rodrigues; Pãmela Rodrigues de Souza Silva; Emerson Soares dos Santos; Diego Ricardo Xavier; Ida Maria Foschiani Dias Baptista; Denise da Costa Boamorte Cortela; Eliane Ignotti; Silvana Margarida Benevides Ferreira (Elsevier, 2022)
Objective: To analyze the prevalence of Mycobacterium leprae detection and the associated factors among social contacts in the school environment of multibacillary cases living in a hyperendemic municipality of the state of Mato Grosso. Methods: Cross-sectional study with 236 social contacts of multibacillary leprosy from public schools and residents in Cuiabá (Mato Grosso) in 2018. The sources of information were interviews and nasal swab tests for molecular analysis by polymerase chain reaction - PCR. For the prevalence ratio estimates, crude and adjusted analyses were performed using robust Poisson regression and their respective confidence intervals (95% CI). The ArcGIS 9.1 software was used for the geographic distribution analyses. Results: The prevalence of detection of M. leprae in social contacts was 14%. A total of 63.6% of the schools surveyed had 5.1% to 50% of the social contacts of leprosy with positive PCR. The analysis of the geographic distribution in the neighborhoods showed a high prevalence of infection, being higher than 50% in some localities. The highest proportion of positive results occurred in the northern region of the city and from a precarious socioeconomic class. Conclusion: The results showed a high prevalence of detection of M. leprae among social contacts in areas with poor socioeconomic conditions. In these regions, there is a greater risk of infection and of getting sick.